Outcome of Laparoscopic Repair of Duodenal Ulcer Perforation Compared with Open Technique - Muhammad Saim, Muhammad Akbar, Saifullah Brohi, Sara Khalid Memon, Ramna Nadeem, Muhammad Zubair (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The surgical treatment of perforated duodenal ulcers is not controversial; however, the best surgical strategy is still up for debate. The perforation closure with an omental patch or without it during surgery is the basis of perforated duodenal ulcers treatment. Laparoscopic surgery can now be used to repair a perforated duodenal ulcer due to developments in minimal access surgery. Aim: In this analysis, the results of open versus laparoscopic repair of perforated duodenal ulcers were compared in terms of operating time, length of hospital stays, postoperative pain and complications after the operation, among other factors. Methods: This prospective comparative study was held at the surgical department of Agha Khan University Hospital, Karachi for one-year duration from January 2022 to December 2022. Patients were divided randomly into two groups, A and B, who underwent operations using laparoscopic and conventional methods, correspondingly, and results were compared. Results: This study found that men between the ages of 51 and 60 were most frequently affected. Laparoscopic group patients experienced much less post-operative pain, need less analgesics, minimum wound infection, and less stay in hospital than open group patients (p 0.05). Conclusions: Laparoscopic repair when performed on carefully chosen patients for perforated duodenal ulcers, it is safe, practical, and produces better outcomes than open surgery. Keywords: Omental patch, laparoscopic repair, open repair, perforated duodenal ulcer